Use of Donkey Milk in Cases of Cow’s Milk Protein Allergies (International Journal of Child Health and Nutrition, 2015)
Human breast milk is the best nutritional support that insure the right development and influence immune status of the newborn infant. However, when it is not possible to breast feeding may be necessary to use commercial infant formulas that mimic, where possible, the levels and types of vitamins, minerals and other nutrients present in human milk. Despite this, some formula-fed infant develops allergy, atopic disease and differences in response to infection with respect to breast-fed infants. Donkey milk may be considered a good substitute for dairy cow’s milk derivatives in feeding children with severe Cow’s Milk Protein Allergy (CMPA) since its composition is closer to human milk compared to other species commonly bred. It has been proposed as an alternative to cow’s milk for children affected by CMPA when it is not possible breast feeding. Donkey milk is characterized by a low casein content, with values very close to human milk, and also total whey protein content in donkey milk is very close to that found in human milk but higher compared to bovine milk. Donkey milk has been used in several clinical trials involving children affected by CMPA because of the low allergenicity of this milk. The results shown in this review confirmed the nutritional characteristics of the protein fractions of donkey milk and the possibility of using donkey milk in feeding children with CMPA, particularly after an adequate lipid integration, including children with multiple food allergies.